Employee attitudes toward suicide prevention and Counseling on Access to Lethal Means: initial findings from an academic medical center implementing the Zero Suicide framework - Jasperson, Rachael A.; Sullivan, Emily; Goldstein, Evan V. (Frontiers in Public Health, 2023)
Introduction: Zero Suicide is a strategic framework designed to transform a healthcare system’s suicide prevention activities. In 2020, University of Utah Health launched a Zero Suicide program and Counseling on Access to Lethal Means (CALM) training for its employees. In 2022, the healthcare system surveyed its workforce’s attitudes toward suicide prevention and CALM. We sought to evaluate employees’ attitudes and behaviors toward suicide prevention and CALM training following the launch of the Zero Suicide program. Methods: A Zero Suicide Workforce Survey was administered online through REDCap to all University of Utah Health employees. The analytic sample included 3,345 respondents. We used two-portion z-tests to compare the proportions of respondents who (1) completed CALM training and (2) did not yet complete the CALM training because they felt it was irrelevant to their position by different employee characteristics. Results: More than half of the respondents in the analytic sample were directly interacting with patients who may be at risk for suicide (57.6%). About 8.4% of the respondents had completed CALM training. Among those who had not yet completed CALM training, 9.5% indicated they did not think CALM was relevant to their job. Respondents who completed CALM training were nearly 4.8 times more likely to report being knowledgeable about suicide warning signs when compared to those who had not yet completed CALM training. Discussion: This evaluation provides important insights from the workforce of a large academic medical center implementing a Zero Suicide program, including insights on opportunities for improving program implementation and evaluation.